Population pharmacokinetic/pharmacodynamic modelling of eplontersen, an antisense oligonucleotide in development for transthyretin amyloidosis. Issue 12 (7th August 2022) - Diep, John K.; Yu, Rosie Z.; Viney, Nicholas J.; Schneider, Eugene; Guo, Shuling; Henry, Scott; Monia, Brett; Geary, Richard; Wang, Yanfeng
Abstract : Aims: Transthyretin‐mediated amyloidosis is a progressive and fatal disease caused by the build‐up of misfolded transthyretin (TTR) protein. Eplontersen is a triantennary N ‐acetyl galactosamine (GalNAc3)‐conjugated antisense oligonucleotide targeting TTR messenger ribonucleic acid (mRNA) to inhibit production of both variant and wild‐type TTR. We aimed to develop a population pharmacokinetic/pharmacodynamic (PK/PD) model for eplontersen and to evaluate the impact of covariates on exposure and response. Methods: Plasma eplontersen and serum TTR concentration data were obtained from two phase 1 studies in healthy volunteers (ClinicalTrials.gov : NCT03728634, NCT04302064). Model development was conducted using a nonlinear mixed‐effects approach. Results: Eplontersen PK was well described by a two‐compartment model. Evaluation of demographics identified significant covariates of lean body mass on clearance and body weight on intercompartmental clearance and volumes of distribution. Population PK modelling showed the absorption rate was 29.6% greater with injection into the abdomen versus the arm. The typical population terminal elimination half‐life was 25.5 days. Serum TTR was well described by an indirect response model with inhibition of TTR production by eplontersen. Maximum fractional inhibition ( I max ) was 0.970 (0.549%RSE) and the half maximal inhibitory concentration (IC50 ) was 0.0283 ng/ml (13.3%RSE). Simulations showed subjects with lower weight had higher exposure (AUC, C max ), while higher C max was observed when comparing site of administration (ratio abdomen/arm = 1.18), but differences in exposure did not significantly impact response at evaluated doses. Conclusion: The exposure‐response relationship of eplontersen was well characterised by the PKPD model. Weight and injection site were found to affect systemic exposure, but this effect does not seem to result in clinically relevant variation in response.